Q-switched ytterbium-doped fiber laser based on evanescent field interaction with lutetium oxide - Jafry, A.A.A.; Kasim, N.; Muhammad, Ahmad Razif; Rosol, Ahmad Haziq Aiman; Yusoff, R.A.M.; Mahyuddin, Mohamad Badrol Hisyam; Zulkipli, Nur Farhanah; Samsamnun, Farina Saffa Mohamad; Harun, Sulaiman Wadi (Optical Society of America, 2019)
We demonstrated lutetium oxide (Lu2O3) deposited onto D-shaped fiber producing Q-switched ytterbium-doped fiber laser (YDFL) with an operating wavelength of 1037 nm. D-shaped fiber Lu2O3 as a saturable absorber (SA) was prepared using a polishing-wheel technique by polishing 2 times to establish an excellent evanescent field interaction between material and light on the surface of the polished region. The SA was deployed into a YDFL to generate Q-switching. The proposed D-shaped fiber Lu2O3 initiated pulses as short as 3.6 µs, with the highest repetition rate of 65.8 kHz. Stability of the SA is proven, as it produced stable pulses within the pump power of 99 to 133 mW with an SNR of 62.13 dB. Q-switched YDFL generates pulses with an output power of 0.93 to 1.99 mW and pulse energy of 17 to 30 nJ. We obtained a laser cavity with the optical-to-optical efficiency of 3.33%, which was the highest among D-shaped fiber-deposited SA materials in YDFL. Therefore, Lu2O3 deposited onto D-shaped fiber can be deployed as an SA in YDFL for a portable Q-switched laser source. © 2019 Optical Society of America.